Role of fibroblasts in nonfibrotic autoimmune skin diseases - He, Yuexi; Han, Zhenxin; Zhang, Qiuli; Liu, Lin; Chang, Jianmin (Molecular medicine (Cambridge, Mass.), 2024)
Autoimmune diseases, a disease characterized by immune imbalance caused by the human immune system mistakenly attacking its own components, include vitiligo, psoriasis and atopic dermatitis (AD). Previous studies on autoimmune diseases have focused mainly on immune cells, keratinocytes and endothelial cells. Fibroblasts, the main cells that secrete the extracellular matrix (ECM) in the dermis, have been studied thoroughly in terms of fibrosis and wound healing. However, an increasing number of studies have shown that fibroblasts play an important role in nonfibrotic autoimmune skin diseases. In this article, the previously reported role of fibroblasts in nonfibrous autoimmune skin diseases such as psoriasis, vitiligo and AD is summarized to provide new ideas for the treatment of this disease.